Nucleosome arrangement in alpha-satellite chromatin of African green monkey cells. - Smith, M R (1984)
By analyzing the accessibility of restriction endonuclease sites in African green monkey alpha-satellite chromatin, we demonstrate the absence of a unique phase relationship between nucleosomes and alpha-satellite DNA. The data indicate a minimum of three different positions for nucleosome cores relative to the alpha-satellite sequence and suggest a random distribution in at least some regions. In addition, while we confirm published reports that staphylococcal nuclease cuts the alpha-satellite sequence in chromatin at a highly preferred site, two-dimensional gel electrophoresis of nuclear digests demonstrates that this site is preferentially cut by staphylococcal nuclease even when it is within the nucleosome core. These data indicate that staphylococcal nuclease is not useful for determining nucleosome positions on alpha-satellite DNA, and perhaps on other specific DNA sequences as well.